Culturally Responsive Digital Pedagogy: Integrating Ethnomycology to Foster Scientific Literacy and Conservation Awareness in High School Students - Fira Wibawanti; Iip Saripah; Asep Kurniawan; Cucu Atikah; Joelash Honra; Rida Oktorida Khastini (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
The post-pandemic transition to contextual and digital learning that is underway as part of the Indonesian merdeka curriculum has created an urgent demand for culturally situated, technology-infused science education. The present study presents a culturally responsive digital pedagogy (CRDP) model, where ethnomycology was incorporated into senior-high-school biology instruction as an approach to enhance scientific literacy and support conservation consciousness. An exploratory sequential mixed-methods design was employed, through in-depth qualitative interviews together with survey-based quantitative data collection with fifteen biology teachers at urban and rural schools across Banten Province. Six types of pedagogical and technological readiness were considered: curriculum fit, instruction strategies, learning medium, instructional materials, ecology fit, and digital assessment tools. Findings showed that teachers had high intentions to integrate ethnomycology into the merdeka curriculum (M = 4.9) and considered digital resources relevant, although availability of contextualized materials and community engagement was limited (M = 4.7). Rural schools indicated greater exposure to local biodiversity, and urban schools were more digitally prepared. The results highlight the importance of providing culturally situated digital modules and instruction to teachers that is tied to biological concepts and local ecological knowledge